2018
DOI: 10.1111/anae.14218
|View full text |Cite
|
Sign up to set email alerts
|

Effect of palpable vs. impalpable cricothyroid membranes in a simulated emergency front‐of‐neck access scenario

Abstract: The Difficult Airway Society 2015 guidelines recommend and describe in detail a surgical cricothyroidotomy technique for the can't intubate, can't oxygenate (CICO) scenario, but this can be technically challenging for anaesthetists with no surgical training. Following a structured training session, 104 anaesthetists took part individually in a simulated can't intubate, can't oxygenate event using simulation and airway models to evaluate how well they could perform these front-of-neck access techniques. Main ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 18 publications
(22 reference statements)
2
13
0
Order By: Relevance
“…17 Psychological barriers can lead to delay in eFONA being performed or to not being performed at all. 18 A more recent study by Pairaudeau and colleagues 19 demonstrated that anaesthetists with limited experience in eFONA could perform the techniques recommended by the DAS guidelines in a timely manner and to a high level of competence after a structured training programme. Reluctance may stem from a scalpel technique being the sole recommended approach, the intimidation of using a scalpel itself, or the potential associated bleeding and trauma.…”
Section: Discussionmentioning
confidence: 99%
“…17 Psychological barriers can lead to delay in eFONA being performed or to not being performed at all. 18 A more recent study by Pairaudeau and colleagues 19 demonstrated that anaesthetists with limited experience in eFONA could perform the techniques recommended by the DAS guidelines in a timely manner and to a high level of competence after a structured training programme. Reluctance may stem from a scalpel technique being the sole recommended approach, the intimidation of using a scalpel itself, or the potential associated bleeding and trauma.…”
Section: Discussionmentioning
confidence: 99%
“…However, the factors of individual stress combined with potential technical issues connected to the ultrasound machine itself, make the use of ultrasound during emergency airway management less convenient [34]. A recent manikin-based study demonstrated the positive effect of training on the scalpel-bougie eFONA performance when the cricothyroid membrane was not palpable [35]. Consequently, there is a possibility that complications associated with the scalpel-bougie technique in our study could be avoided if regular wet lab or manikin training was implemented.…”
Section: Plos Onementioning
confidence: 99%
“…Performing an emergency front of neck airway (eFONA) in this situation can be life‐saving but is associated with a significant failure rate . This has prompted discussion on methods of improving eFONA training; simulation training improves adherence to CICO algorithms and eFONA technical skills . The 2015 Difficult Airway Society (DAS) guidelines advocate a scalpel‐based technique and recommended regular training, whereas the 4th National Audit Project of the Royal College of Anaesthetists (NAP4) and the DAS recommended that “ all anaesthetists must be trained in emergency cricothyroidotomy and keep their skills up to date ” .…”
Section: Introductionmentioning
confidence: 99%